Light-Induced Subpicosecond Lattice Symmetry Switch in MoTe_{2} - M. Y. Zhang (American Physical Society, 2019)
The recent development of ultrashort laser pulses allows for optical control of structural and electronic properties of complex quantum materials. The layered transition-metal dichalcogenide MoTe_{2}, which can crystallize into several different structures with distinct topological and electronic properties, provides possibilities to control or switch between different phases. In this study, we report a photoinduced subpicosecond structural transition between the type-II Weyl semimetal phase and normal-semimetal phase in bulk crystalline MoTe_{2} by using ultrafast pump-probe and time-resolved second-harmonic-generation spectroscopy. The phase transition is most clearly characterized by the dramatic change of the shear oscillation mode and the intensity loss of second-harmonic generation. This work opens up new possibilities for ultrafast manipulation of the topological properties of solids, enabling potentially practical applications for a topological switch device with ultrafast excitations.